GENRES DIDACTIC SEQUENCES IN THE CONTEXT OF MASTER'S RESEARCH IN LETTERS: CONTRIBUTIONS TO TEACHER TRAINING AND LANGUAGE TEACHING - Alves, Maria de Fátima; Catanduba, Edilma Lucena (Revista de Letras, 2022)
This article aims to describe and present the results of two studies which focus on didactic sequences, in the light of the studies of Joaquim Dolz and Shneuwly, as a relevant methodological proposal for the teaching of textual genres. The research, of an interventionist nature, was developed within the scope of the Professional Master's Degree - PROFLETRAS, at the State University of Paraíba (UEPB), Campus III, and the Institutional Master's Degree in the Postgraduate Program in Language and Teaching (PPGLE), at the Federal University of Campina Grande (UFCG). This qualitative research is linked to the field of Applied Linguistics and based on the studies of Sociodiscursive Interactionism. The results indicate that, through the researchers’ training processes, the research subjects, who are teachers of Basic Education, started to consider the didactic sequence as a methodological tool for native language teaching, placing an emphasis on language capacities, such as production context and linguistic-discursive aspects, in the proposals of text production of a certain genre.